A Teaching-Learning Proposal Focused on the Analysis of the Energy Roadway "Step by Step" [Una Propuesta de Enseñanza-Aprendizaje Centrada en el Análisis del Camino de la Energía "Paso a Paso"] - Soto-Alvarado, M (Universidad de Cádiz y Asociación de Profesores Amigos de la Ciencia, 2019)
The scholar model of energy and its energy-related concepts (energy as a function of state, transfer, conservation and degradation) represent a challenge for teachers and students, since it implies changing the way to see the physical phenomena, from the mechanics to the energetic view. To build this model "step by step" we present an instructional sequence, analysing both theoretically and experimentally a wheel braking process, using a simple experimental set-up. © 2019 Universidad de Cádiz y Asociación de Profesores Amigos de la Ciencia. All Rights Reserved.